Discordant Spirometry and Impulse Oscillometry Assessments in the Diagnosis of Small Airway Dysfunction - Lu, Lifei; Peng, Jieqi; Zhao, Ningning; Wu, Fan; Tian, Heshen; Yang, Huajing; Deng, Zhishan; Wang, Zihui; Xiao, Shan; Wen, Xiang; Zheng, Youlan; Dai, Cuiqiong; et al. (Frontiers in Physiology, 2022)
Background and objective: Spirometry is commonly used to assess small airway dysfunction (SAD). Impulse oscillometry (IOS) can complement spirometry. However, discordant spirometry and IOS in the diagnosis of SAD were not uncommon. We examined the association between spirometry and IOS within a large cohort of subjects to identify variables that may explain discordant spirometry and IOS findings. Methods: 1836 subjects from the ECOPD cohort underwent questionnaires, symptom scores, spirometry and IOS, and 1318 subjects were examined by CT. We assessed SAD with R5-R20 > the upper limit of normal (ULN) by IOS and two of the three spirometry indexes (maximal mid-expiratory flow (MMEF), forced expiratory flow (FEF)50%, and FEF75%) < 65% predicted. Multivariate regression analysis was used to analyze factors associated with SAD diagnosed by only spirometry but not IOS (spirometry-only SAD) and only IOS but not spirometry (IOS-only SAD) and line regression was used to assess CT imaging differences. Results: There was a slight agreement between spirometry and IOS in the diagnosis of SAD (kappa 0.322, P < 0.001). Smoking status, phlegm, drug treatment, and family history of respiratory disease were factors leading to spirometry-only SAD. Spirometry-only SAD had more severe emphysema and gas trapping than IOS-only SAD in abnormal lung function. However, in normal lung function subjects, there was no statistical difference in emphysema and gas trapping between discordant groups. The number of IOS-only SAD was nearly twice than that of spirometry. Conclusions: IOS may be more sensitive than spirometry in the diagnosis of SAD in normal lung function subjects. But in patients with abnormal lung function, spirometry may be more sensitive than IOS to detect SAD patients with clinical symptoms and CT lesions.